Giải phương trình: √(15 – x) + √(3 – x) = 6

Question

Giải phương trình: √(15 – x) + √(3 – x) = 6

in progress 0
Ivy 2 tháng 2021-10-05T09:37:50+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-10-05T09:38:51+00:00

    Đáp án:

    Giải thích các bước giải:

    ĐK -9=

    $\sqrt{15-x} + \sqrt{3-x} =6$

    $<=> 15-x+3-x+2\sqrt{(15-x)(3-x)} =36$

    $<=>\sqrt{x^2-18x+45} =x+9$

    $<=> x^2-18x+45=x^2+18x+81$

    $<=>36x=-36$

    $<=>x=-1 (TMĐK)$

    Vậy$ x=-1$

    0
    2021-10-05T09:39:42+00:00

    Đáp án:

    Giải thích các bước giải:

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )